Interfacial acidity in ligand-modified ruthenium nanoparticles boosts the hydrogenation of levulinic acid to gamma-valerolactone. Issue 10 (13th October 2016) - Albani, Davide; Li, Qiang; Vilé, Gianvito; Mitchell, Sharon; Almora-Barrios, Neyvis; Witte, Peter T.; López, Núria; Pérez-Ramírez, Javier
Abstract : Supported Ru-HHDMA nanoparticles are superior catalysts for the continuous-flow hydrogenation of levulinic acid to γ-valerolactone due to the bifunctional nature of the metal–ligand interface. Abstract : Gamma-valerolactone (GVL), a versatile renewable compound listed among the top 10 most promising platform chemicals by the US Department of Energy, is produced via hydrogenation of levulinic acid (LA). The traditional high-loading ruthenium-on-carbon catalyst (5 wt% Ru) employed for this transformation suffers from low metal utilisation and poor resistance to deactivation due to the formation of RuO x species. Aiming at an improved catalyst design, we have prepared ruthenium nanoparticles modified with the water-soluble hexadecyl(2-hydroxyethyl)dimethylammonium dihydrogen phosphate (HHDMA) ligand and supported on TiSi2 O6 . The hybrid catalyst has been characterised by ICP-OES, elemental analysis, TGA, DRIFTS, H2 -TPR, STEM, EDX, 31 P and 13 C MAS-NMR, and XPS. When evaluated in the continuous-flow hydrogenation of LA, the Ru-HHDMA/TiSi2 O6 catalyst (0.24 wt% Ru) displays a fourfold higher reaction rate than the state-of-the-art Ru/C catalyst, while maintaining 100% selectivity to GVL and no sign of deactivation after 15 hours on stream. An in-depth molecular analysis by Density Functional Theory demonstrates that the intrinsic acidic properties at the ligand–metal interface under reaction conditions ensure that the less energy demanding path is followed. The reaction does not obey the expected cascade mechanism and intercalates hydrogenation steps, hydroxyl/water eliminations, and ring closings to ensure high selectivity. Moreover, the interfacial acidity increases the robustness of the material against ruthenium oxide formation. These results provide valuable improvements for the sustainable production of GLV and insights for the rationalisation of the exceptional selectivity of Ru-based catalysts.